The Wnt signaling cascade in the pathogenesis of osteoarthritis and related promising treatment strategies - Cheng, Jinchao; Li, Min; Bai, Ruijun (Frontiers in Physiology, 2022)
Abstract Osteoarthritis (OA) is the most prevalent joint disease characterized by degradation of articular cartilage, synovial inflammation, and changes in periarticular and subchondral bone. Recent studies have reported the Wnt signaling cascades play an important role in the development, growth and homeostasis of joints. The Wnt signaling cascade should be tightly regulated to maintain the homeostasis of the cartilage for the purpose of either over-activation or suppression of Wnt/ β-catenin could lead to the OA. This review summarizes the role and mechanism of the canonical WNT cascade and noncanonical WNT cascades experiments in vivo and in vitro. The Wnt cascade is controlled by several agonists and antagonists in the extracellular and the cytoplasm. These antagonists and agonists serve as key molecules in drug intervention of the Wnt pathway and may provide some potential approaches for the treatment of OA. However, the complexity of the Wnt signaling cascade and the pharmaceutical effect on the mechanism are still not fully understood which forced us to further research and develop efficient therapeutic approaches to treat OA.